2020
DOI: 10.1093/abm/kaaa073
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Social Distancing Intention and Behavior During the COVID-19 Pandemic: An Integrated Social Cognition Model

Abstract: Background Social distancing is a key behavior to minimize COVID-19 infections. Identification of potentially modifiable determinants of social distancing behavior may provide essential evidence to inform social distancing behavioral interventions. Purpose The current study applied an integrated social cognition model to identify the determinants of social distancing behavior, and the processes involved, in the context of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
169
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 169 publications
(194 citation statements)
references
References 35 publications
20
169
1
4
Order By: Relevance
“…Moreover, self-reported protective actions could be inaccurate because of response-set biases (e.g., acquiescence), social desirability, or inaccurate memory. However, self-report is a standard source of information in studies measuring health-protective behaviors in airborne infectious diseases and the COVID-19 outbreak ( Cowling et al, 2010 ; Dryhurst et al, 2020 ; Hagger et al, 2020 ; Lin et al, 2020 ). Future studies might include social desirability scales to check for under- or over-reporting as well as attention checks to improve the validity of self-report data.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, self-reported protective actions could be inaccurate because of response-set biases (e.g., acquiescence), social desirability, or inaccurate memory. However, self-report is a standard source of information in studies measuring health-protective behaviors in airborne infectious diseases and the COVID-19 outbreak ( Cowling et al, 2010 ; Dryhurst et al, 2020 ; Hagger et al, 2020 ; Lin et al, 2020 ). Future studies might include social desirability scales to check for under- or over-reporting as well as attention checks to improve the validity of self-report data.…”
Section: Discussionmentioning
confidence: 99%
“…The predictive role of intentions, perceived severity and susceptibility, and attitudes is compatible with the existing literature that also shows a similar effect. Moreover, a recent study examined the determinants of social distancing in the context of the COVID-19 pandemic from the theory of planned behavior viewpoint [ 21 ]. Their findings indicated that intention and habit were significant predictors of social distancing behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Ensuing research examining future outbreaks should systematically investigate existing models in full and compare them to assess their predictive validity and theoretical value. Indeed, several recently published studies have adopted one model through which they examined preventive behavior in the current pandemic context, such as the theory of planned behavior [ 21 ] or the health action process approach [ 29 ]. Also, since the present survey was launched, several scales were developed that assess both COVID-19 related health behavior [ 24 ] and specific predictors such as fear [ 29 ], anxiety [ 30 ], obsession [ 31 ], and stress [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our study was conducted starting immediately after the national lockdown and it was very difficult to collect data that were not based on self-reported responses, due to the limitations that had been imposed, as regards the obligation to maintain physical distancing, and the difficulty of having face-to-face meetings and of bringing participants together in the same place. Future studies might use technological devices, such as phone apps based on GPS tracking ( Hagger et al., 2020 ) as different ways of measuring PDB, although similar approaches would need to comply with the privacy rights of the participants. Finally, consistently with the aims of our study, we measured adolescents’ emotions over the period of a month.…”
Section: Discussionmentioning
confidence: 99%